Correlation between mitochondrial DNA copy number, Klotho protein, myostatin and frailty in elderly patients with sarcopenia - Zhou Yanyan; Zhao Xulan; Zhang Shiyang; Xia Song; Zhang Junhui; Liang Fang (Guoji laonian yixue zazhi, 2025)
[Objective] To investigate the correlation of mitochondrial DNA copy number (mtDNAcn), Klotho protein, myostatin (MSTN) and their combination with physical frailty in elderly patients with sarcopenia. [Methods] A total of 172 elderly patients with sarcopenia admitted to Shijiazhuang People’ss Hospital from January 2022 to August 2024 were selected and divided into sarcopenia group and fraity combined sarcopenia group(combined group) according to Fried frailty scale score.General data and clinical data were collected to detect mtDNAcn, Klotho protein and MSTN levels in blood, and the correlation between the above parameters and the combination of the three and debilitating status was analyzed. [Results] There was no significant difference in gender, body mass index, duration of sarcopenia, smoking, alcohol abuse and underlying diseases between the two groups (P>0.05); compared with sarcopenia group, combined group had higher age, interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), lower serum albumin (ALB), 25-(OH)D, grip strength, pace, and skeletal muscle density, and the difference was statistically significant (P<0.05); compared with sarcopenia group, combined group had lower mtDNAcn and Klotho protein levels and higher MSTN levels, and logistic regression analysis showed that MSTN, age, IL-6, and TNF-α were all risk factors for frailty with sarcopenia, while mtDNAcn, Klotho protein, ALB, 25-(OH)D, and grip strength were protective factors (P<0.05); receiver operating characteristic curve analysis showed that MSTN, age, IL-6, and TNF-α were all risk factors for frailty with sarcopenia, while mtDNAcn, Klotho protein, ALB, and 25-(OH)D, and grip strength were protective factors (P<0.05); The area under the curve for combined prediction of frailty status in elderly sarcopenia patients was the largest, and the sensitivity and specificity at their cutoff values were 0.926 and 0.739, respectively. mtDNAcn, Klotho protein, and MSTN all had predictive value for frailty status in elderly sarcopenia patients (P<0.05). [Conclusion] MtDNAcn and Klotho protein levels are protective factors for frailty in elderly sarcopenia patients, while MSTN levels are risk factors, and the above indicators have evaluation value for frailty status in elderly sarcopenia patients.